2001
DOI: 10.1093/brain/124.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Brain responses to changes in bladder volume and urge to void in healthy men

Abstract: Knowledge of how changes in bladder volume and the urge to void affect brain activity is important for understanding brain mechanisms that control urinary continence and micturition. This study used PET to evaluate brain activity associated with different levels of passive bladder filling and the urge to void. Eleven healthy male subjects (three left- and eight right-handed) aged 19-54 years were catheterized and the bladder filled retrogradely per urethra. Twelve PET scans were obtained during two repetitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
213
1
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(242 citation statements)
references
References 51 publications
14
213
1
5
Order By: Relevance
“…In normal controls some of the brain regions responding to bladder filling (PAG, insula, frontal cortex, Supplementary Tables 5 and 6 Figure 6 is close to a similar region activated by increasing bladder volume in a PET study (Athwal et al, 2001). The hypothalamic region in Supplementary Table 6 and Figure 3 is identical to one responding to decreased urge to void in the same study; it appears to be the perifornical area of the hypothalamus, which in the cat has direct monosynaptic access to the PMC (Holstege, 2005).…”
Section: Normal Responses and Effect Of Agingmentioning
confidence: 62%
See 2 more Smart Citations
“…In normal controls some of the brain regions responding to bladder filling (PAG, insula, frontal cortex, Supplementary Tables 5 and 6 Figure 6 is close to a similar region activated by increasing bladder volume in a PET study (Athwal et al, 2001). The hypothalamic region in Supplementary Table 6 and Figure 3 is identical to one responding to decreased urge to void in the same study; it appears to be the perifornical area of the hypothalamus, which in the cat has direct monosynaptic access to the PMC (Holstege, 2005).…”
Section: Normal Responses and Effect Of Agingmentioning
confidence: 62%
“…Bladder control is exercised by the brain via a long-loop spinobulbospinal reflex pathway that includes the midbrain periaqueductal gray (PAG) and the pontine micturition center (PMC), which in turn are controlled by a supratentorial network. The main network landmarks are known from animal and clinical observations, and from functional imaging by positron emission tomography (PET) (Athwal et al, 2001;Blok et al, 1997b;Kitta et al, 2006;Matsuura et al, 2002;Nour et al, 2000) or functional magnetic resonance imaging (fMRI) (Di Gangi Herms et al, 2006;Griffiths et al, 2005;KuhtzBuschbeck et al, 2005;Seseke et al, 2006;Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) 10 . Early studies using functional brain imaging revealed that, the ACC is involved in monitoring bladder filling 11 , withholding urine, and starting micturition 12,13 . However, subsequent studies suggested more complex functions such as a role in 14 integrating afferent information and internal motivational states 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies using functional brain imaging revealed that, the ACC is involved in monitoring bladder filling 11 , withholding urine, and starting micturition 12,13 . However, subsequent studies suggested more complex functions such as a role in 14 integrating afferent information and internal motivational states 12 . Functional brain imaging studies have shown that there are increased responses in the ACC during withholding urine in normal volunteers 14 and that the ACC is activated when patients have the sensation of urgency and when OAB patients tighten pelvic floor and sphincter muscles and relax the bladder, in order to maintain continence 2 .…”
Section: Discussionmentioning
confidence: 99%